Pengaruh Kepemimpinan Transformasional dan Motivasi Kerja Terhadap Kinerja Pegawai Pada Kantor Sekretariat DPRD Provinsi Sumatera Barat - Khairil Aswan,; Reza Desma Yandiana, (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
The purpose of this study was to examine the effect of the Transformational Leadership variable on employee performance at the DPRD Secretariat Office of West Sumatra Province. to examine the effect of work motivation variables on employee performance at the DPRD Secretariat Office of West Sumatra Province. Collecting data by distributing questionnaires to 94 respondents using saturated sampling technique, where all members of the population are sampled, using data processing techniques, namely instrument testing, classical assumption testing, multiple linear regression testing and t-test with the help of the SPSS application. The results of the study show that transformational leadership has a positive and significant effect on employee performance, work motivation has a positive and significant effect on employee performance.